Distributed and Parallel Systems From Cluster to Grid Computing - Kacsuk, Peter; Fahringer, Thomas; Nemeth, Zsolt (Springer US : Imprint: Springer, 2007)
The sixth Austrian-Hungarian Workshop on Distributed and Parallel Systems is organized jointly by the University of Innsbruck, and the MTA SZTAKI Computer and Automation Research Institutute (DAPSYS 2006). Distributed and Parallel Systems: From Cluster to Grid Computing is mainly devoted to general algorithmic aspects of parallel and distributed computing and grid computing. This book includes a good overview of recent advances in various aspects of parallel and distributed computing. Distributed and Parallel Systems: From Cluster to Grid Computing brings together contributed chapters by world class leaders in this field. This volume also includes various crucial questions tied to the infrastructure and advanced problems and challenges of grid computing. Distributed and Parallel Systems: From Cluster to Grid Computing is designed for practitioners and researchers in industry. This book is also suitable for graduate-level students in computer science and engineering. .